Inclusive double-pomeron exchange at the fermilab tevatron p p collider. - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2004)
We report results from a study of events with a double-Pomeron exchange topology produced in p p collisions at sqrt[s]=1800 GeV. The events are characterized by a leading antiproton and a large rapidity gap on the outgoing proton side. We find that the differential production cross section agrees in shape with predictions based on Regge theory and factorization, and that the ratio of double-Pomeron exchange to single diffractive production rates is relatively unsuppressed as compared to the O(10) suppression factor previously measured in single diffractive production.